2017
DOI: 10.3748/wjg.v23.i44.7888
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-125a but not miR-125b is decreased in active disease status and negatively correlates with disease severity as well as inflammatory cytokines in patients with Crohn’s disease

Abstract: AIMTo determine the association of circulating miR-125a/b expression with the risk and disease severity of Crohn’s disease (CD), and with inflammatory cytokines.METHODSPlasma samples were collected from patients with active CD (A-CD), or CD in remission (R-CD) and from healthy controls (HCs). The levels of the inflammatory cytokines interleukin-17 (IL-17), tumour necrosis factor-α (TNF-α), and interferon-γ (IFN-γ) were measured by enzyme-linked immunosorbent assay. The expression of miR-125a/b was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…10 Additionally, according to the previous studies that miR-125a overexpression reduced the various kinds of cell proliferation, such as endothelial cells and adipocytes, psoriatic patients with miR-125a overexpression may experience reduced epidermal cell proliferation and epidermal hyperplasia; thus, miR-125a overexpression was associated with less risk of psoriasis. 14,23,24 In our present study, we found that baseline miR-125a expression was lower in PASI-75 responders compared with PASI-75 non-responders, and logistic regression model analysis exhibited that miR-125a was an independent predictive factor for worse PASI-75 response to ETN at M6 in psoriatic patients. miRNA-125a is also reported to serve as a potential prognostic biomarker in autoimmune and inflammatory diseases.…”
Section: Discussionsupporting
confidence: 59%
“…10 Additionally, according to the previous studies that miR-125a overexpression reduced the various kinds of cell proliferation, such as endothelial cells and adipocytes, psoriatic patients with miR-125a overexpression may experience reduced epidermal cell proliferation and epidermal hyperplasia; thus, miR-125a overexpression was associated with less risk of psoriasis. 14,23,24 In our present study, we found that baseline miR-125a expression was lower in PASI-75 responders compared with PASI-75 non-responders, and logistic regression model analysis exhibited that miR-125a was an independent predictive factor for worse PASI-75 response to ETN at M6 in psoriatic patients. miRNA-125a is also reported to serve as a potential prognostic biomarker in autoimmune and inflammatory diseases.…”
Section: Discussionsupporting
confidence: 59%
“…Finally, miR‐125‐a, known to be involved in macrophage differential activation through downregulation of TNF‐α‐induced protein 3 (TNFAIP3) (Graff, Dickson, Clay, McCaffrey, & Wilson, ) and of the inflammatory transcription factor Kruppel‐like factor 13 (KLF13) (Banerjee, Cui, et al, ), has been recently found to be upregulated in reactive microglia and in extracellular vesicles (EVs) thereof (Prada et al, ). Few glycolytic enzymes, including enolase‐1 (ENO‐1), HK2 (F. Jin et al, ; C. M. Sun, Wu, Zhang, Shi, & Chen, ) and phosphofructokinase (PFK1) are miR‐125‐a validated targets (Table 1). Consistently, miR‐125‐a decreases the uptake of glucose and the production of lactate, and the levels of ATP and ROS in other cell types (F. Jin et al, ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%
“…Besides, lncRNA ANRIL also facilitates the pathological progression in pulmonary diseases, and for instance, lncRNA ANRIL promotes cells proliferation and metastasis in non–small‐cell lung cancer (NSCLC) . MicroRNA‐125a (miR‐125a), as one of the target genes of lncRNA ANRIL, is downregulated in several inflammatory diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis, and Crohn's disease . In addition, decreased level of miR‐125a is associated with lung inflammation and acute alveolar hemorrhage in SLE patients by recruiting of neutrophils .…”
Section: Introductionmentioning
confidence: 99%